Una ciudad diversa. Entre el ideal urbano y la sociedad barroca: Valladolid de Michoacán, siglos XVI-XVIII - González Correa, Alexis Uriel (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
When the European world-economy began to expand in the second half of the fifteenth century, Portuguese and Spaniards took to the trans-Atlantic adventure that culminated in the invention of new epistemological world. With him, suddenly appeared a way to imagine the totalization of human life under the ideal of early European modernity. In this concert, the city emerged as an element that allowed expanding the frontier of the European world, clinching the Spanish dominion in America, and more importantly, which could crystallize a civilizational choice. However, among the urban ideal of Hispanics and the reality imposed in the late sixteenth century, it emerged an alternative characterized by a built from improvisation and the motley, where extravagance and theatricality were able to discontinue the European totalizing project company.

Cuando la economía-mundo europea comenzó a expandirse en la segunda mitad del siglo XV, portugueses y españoles se lanzaron a la aventura trasatlántica que culminó con la invención epistemológica del nuevo mundo. Con él, pronto apareció una forma de imaginar la totalización de la vida humana bajo el ideal de una temprana modernidad europea. En ese concierto, lo urbano emergió como un elemento que permitía expandir la frontera del mundo europeo, que afianzaba el dominio español en América, y más importante, en el que se podía cristalizar una elección civilizatoria. No obstante, entre el ideal urbano de los hispanos y la realidad impuesta a finales del siglo XVI, surgió una alternativa caracterizada por una sociedad construida desde la improvisación y el abigarramiento, donde la extravagancia y la teatralidad fueron capaces de suspender el proyecto totalizador europeo.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2016-1047; Ideal urbano; Modernidad; Sociedad colonial; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/291